1990
DOI: 10.1177/146642409011000309
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Patterns in Saudi Arabian Children

Abstract: IN A STUDY of 2006 school children living in two

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
3
15
1
Order By: Relevance
“…A similar study conducted in Saudi Arabia also sheds light on this association between parental atopy ( p value <0.007 [31]) and the appearance of allergy symptoms ( p < 0.01 [30]) among children. In light of these findings, it can be hypothesized that atopic diseases are inherited in children; however, the mode of inheritance is yet to be discovered (32).…”
Section: Discussionmentioning
confidence: 96%
“…A similar study conducted in Saudi Arabia also sheds light on this association between parental atopy ( p value <0.007 [31]) and the appearance of allergy symptoms ( p < 0.01 [30]) among children. In light of these findings, it can be hypothesized that atopic diseases are inherited in children; however, the mode of inheritance is yet to be discovered (32).…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, in country districts and villages a much more traditional lifestyle is maintained. Previous studies have suggested that doctor-diagnosed asthma occurs in 4-17% of urban Saudi children [22,23].…”
mentioning
confidence: 99%
“…About 10% of children nationally suffer from bronchial asthma, and even much higher (18%) suffer from allergic rhinitis. Regional differences in the prevalence pattern 7 of both bronchial asthma and allergic rhinitis were clear in three regions, indicating the possible influence of some environmental factor(s) in the sensitization and elicitation of symptoms in the allergic population of the regions.…”
Section: Accepted For Publication 28 May 1996 Received 5 December 1995mentioning
confidence: 99%
“…Health care facilities, including hygiene, in the Kingdom, are considered to be excellent. According to our recent prevalence study, 7 bronchial asthma emerged to be a common disease in children. About 10% of children nationally suffer from bronchial asthma, and even much higher (18%) suffer from allergic rhinitis.…”
Section: Accepted For Publication 28 May 1996 Received 5 December 1995mentioning
confidence: 99%